Doing something for us e for our village: “Lorto project” in the opinion of Chiuduno lower secondary school students - Zappella, Emanuela (Formazione & insegnamento, 2019)
The relationship with nature will be of vital importance for the future of our planet; for this reason, numerous environmental education experiences are active in schools both at nationally and internationally levels. The students of the Secondary School of Chiuduno (Bergamo), who took part in the “Lorto project”, told their opinions and feelings through a written interview. The materials were transcribed and analyzed through the construction of “conceptual boxes” (Della Porta, 2014). The results show the importance of environmental education not only with respect to didactic knowledge but, more generally, with the acquisition of social skills that can be spent within society.